Long Non-coding RNA Regulation of Mesenchymal Stem Cell Homeostasis and Differentiation: Advances, Challenges, and Perspectives - Yang, Yanlei; Liu, Suying; He, Chengmei; Chen, Zhilei; Lyu, Taibiao; Zeng, Liuting; Wang, Li; Zhang, Fengchun; Chen, Hua; Zhao, Robert Chunhua (Frontiers in Cell and Developmental Biology, 2021)
Given the self-renewal, multi-differentiation, immunoregulatory, and tissue maintenance properties, mesenchymal stem cells (MSCs) are promising candidates for stem cell-based therapies. Breakthroughs have been made in uncovering MSCs as key contributors to homeostasis and the regenerative repair of tissues and organs derived from three germ layers. MSC differentiation into specialized cell types is sophisticatedly regulated, and accumulating evidence suggests long non-coding RNAs (lncRNAs) as the master regulators of various biological processes including the maintenance of homeostasis and multi-differentiation functions through epigenetic, transcriptional, and post-translational mechanisms. LncRNAs are ubiquitous and generally referred to as non-coding transcripts longer than 200 bp. Most lncRNAs are evolutionary conserved and species-specific; however, the weak conservation of their sequences across species does not affect their diverse biological functions. Although numerous lncRNAs have been annotated and studied, they are nevertheless only the tip of the iceberg; the rest remain to be discovered. In this review, we characterize MSC functions in homeostasis and highlight recent advances on the functions and mechanisms of lncRNAs in regulating MSC homeostasis and differentiation. We also discuss the current challenges and perspectives for understanding the roles of lncRNAs in MSC functions in homeostasis, which could help develop promising targets for MSC-based therapies.